Menakar Ulang Gairah Relevansi Gereja - Adiprasetya, Joas (STT BNKP Sundermann, 2024)
This article aims to examine the myth of relevance lived by churches in Indonesia, which understands that the church must be relevant to the life issues in the world. This article takes a different path, namely, to critically question the assumption of relevance and proposing a different spiritual and ecclesial approach. Such an approach suggests that the church must be irrelevant to the world, in order to maintain its identity and calling received from the Triune God. The study is characteristically more conceptual than contextual, therefore a review of the context of churches in Indonesia is not specifically presented. A comparative study of the thoughts of Henri J. M. Nouwen, Timothy Radcliffe, Jonathan Menezes, and Mark Sayers is carried out analytically, which is then summarized through James Hunter's thoughts on the concept of “faithful presence,” which helps churches to maintain the tension between their identity and their relationship with the world.